Investigating the Impact of Oil Price and Exchange Rate Uncertainty on Stock Return using Whitening Linear Transformation and Vector Autoregressive Model - Farahani, Mohammad; Hanzaee, Alireza Heidarzadeh (UI Scholars Hub, 2018)
This study aims at investigating the impact of oil price and exchange rate uncertainty on stock returns in Tehran Securities Exchange (TSE). To this end,